Biochemical Characterization of Probiotics Available in Bangladesh (Journal of Scientific Research, 2016)
The pervasive beneficial effects of probiotics are important for the maintenance of mammalian homeostasis. The probiotic products are consumed by people in their various forms available in Bangladesh. In this context, this study is taken into consideration to identify and characterize bacteria to confirm the scientific data needed for improvement in probiotic products as current therapies. Five probiotic samples were collected from pharmaceutical companies available in the retail pharmacy, Rajshahi. The probiotic samples are tested before expiration dates as marked on manufacturer packages. The culture media used were Czapek Dox (pH 5.3), MRS and nutrient broth and agar for the investigation of lactic acid bacteria. The identified lactic acid bacteria (LAB) were lactobacillus acidophyllus (LAB 1), Lactobacillus bulgaricus (LAB 2), Lactococcus lactis (LAB 3) and Biffidobacterium biffidum (LAB 4) based on morphological characteristics, catalase activities, milk coagulation, carbohydrate fermentation profiles, resistance to antibiotics and other biochemical tests. The rejuvenation of probiotics particularly LAB from the probiotic samples can be used in other purposes such as biopreservation of lemon, orange juices with better tastes and fermented products like curds as well as hygienic qualities of other dairy products.